Development and Validation of the Joyful Learning of Reading Scale for EFL Student - Elisa, Lusi; Setiyadi, Ag. Bambang; Sumarti (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
This study develops and validates the Joyful Learning of Reading Scale (JLR), an instrument designed to measure the enjoyment, engagement, and intrinsic motivation of students in the context of reading English as a Foreign Language (EFL). The research utilizes a quantitative approach, with the scale being tested for its psychometric properties using Rasch Model analysis. A sample of 244 EFL students from Indonesian universities participated in the study, providing data on their experiences with reading activities. The results confirm that the JLR scale is both valid and reliable, as evidenced by a Cronbach’s alpha of 0.92 and a Person Separation reliability of 0.88. The scale effectively captures the emotional and cognitive dimensions of reading, showing that it can measure a range of student engagement and motivation levels. By using the JLR scale, educators can assess how well their teaching strategies promote Joyful Learning, helping to create more engaging and motivating learning environments. The study highlights the importance of fostering intrinsic motivation and enjoyment in reading, as these factors significantly contribute to improving students' reading comprehension and overall academic performance. The JLR scale, therefore, serves as an important tool for enhancing the quality of EFL education.